The complete works of James Shirley - Shirley, James 1596-1666 (Oxford University Press, 2022)
The Complete Works of James Shirley contains a corpus of around 50 works, including plays, poems, grammars and prose. Shirley (1596-1666) is arguably the most significant dramatic writer of the late English Renaissance, but the last scholarly collections of his plays appeared in the nineteenth century and this Oxford edition is the first to provide a complete works. Shirley was a quintessentially Caroline writer whose work echoes and builds upon the art of his Elizabethan and Jacobean predecessors. Caroline drama would be unthinkable without Shirley, who enjoyed a great reputation as a playwright both at court and in the theatres. This comprehensive scholarly edition provides well-annotated modernized texts of the full range of Shirley's remarkable output, not0just of his favourite plays. Each work is introduced by an essay examining dating and background, sources, context and performance, and by one which discusses the textual situation and production of the early editions. An extensive footnoted commentary is provided for all texts, to help the modern reader with difficult passages, explain historical usage and customs and to clarify meaning in context.
Keywords: Shirley, James / 1596-1666